1970
DOI: 10.1104/pp.45.5.632
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chloramphenicol on Amino Acid Incorporation by Chloroplasts and Comparison with the Effect of Chloramphenicol on Chloroplast Development in Vivo

Abstract: Amino acid incorporation into protein by chloroplasts and chloroplast ribosomes is more sensitive to inhibition by chloramphenicol than amino acid incorporation into protein by cytoplasmic ribosomes (3,4). Chloramphenicol also inhibits the formation of some chloroplast enzymes without affecting cell division in Euglena (11) or leaf development in bean (8,9). Chloramphenicol also selectively increases the proportion of 70 S ribosomes present as polysomes (6). Chloramphenicol is bound to chloroplast 70 S ribosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

1970
1970
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…We found a decreased rate of the chlorophyll formation of the treated leaves and a decrease of the chlorophyll ajb ratio, similar to the results of Margulies and Brubaker (1970), Nikolaeva et al (1970) and Karimov et al (1974). The measured chlorophyll alb ratio of the treated leaves suggests a shifting of their pigment composition towards that of photosystem II.…”
Section: Discussionsupporting
confidence: 92%
“…We found a decreased rate of the chlorophyll formation of the treated leaves and a decrease of the chlorophyll ajb ratio, similar to the results of Margulies and Brubaker (1970), Nikolaeva et al (1970) and Karimov et al (1974). The measured chlorophyll alb ratio of the treated leaves suggests a shifting of their pigment composition towards that of photosystem II.…”
Section: Discussionsupporting
confidence: 92%
“…Others have also reported that 80 to 90% inhibition was the maximum for concentrations of CAP and CCH in the range of 5 to 100 ,ug/ml (6,9,13,16). The inhibitions by each inhibitor alone were not additive in the combination.…”
Section: Discussionmentioning
confidence: 90%
“…Puromycin and fusidic acid are potent inhibitors of protein synthesis of both prokaryotic and eukaryotic systems (Carpenter and Cherry, 1966;Goswami et al, 1973). Although chloramphenicol is a specific inhibitor of protein synthesis of prokaryotic systems, there is good evidence that chloramphenicol inhibits protein synthesis in higher plants, probably by inhibiting synthesis of chloroplast-encoded proteins (Margulies and Brubaker, 1970).…”
Section: Inhibitors Of Protein Synthesismentioning
confidence: 99%